Early Access to the Cardiac Catheterization Laboratory for Patients Resuscitated From Cardiac Arrest Due to a Shockable Rhythm: The Minnesota Resuscitation Consortium Twin Cities Unified Protocol - Santiago Garcia; Todd Drexel; Wobo Bekwelem; Ganesh Raveendran; Emily Caldwell; Lucinda Hodgson; Qi Wang; Selcuk Adabag; Brian Mahoney; Ralph Frascone; Gregory Helmer; Charles Lick; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundIn 2013 the Minnesota Resuscitation Consortium developed an organized approach for the management of patients resuscitated from shockable rhythms to gain early access to the cardiac catheterization laboratory (CCL) in the metro area of Minneapolis‐St. Paul. Methods and ResultsEleven hospitals with 24/7 percutaneous coronary intervention capabilities agreed to provide early (within 6 hours of arrival at the Emergency Department) access to the CCL with the intention to perform coronary revascularization for outpatients who were successfully resuscitated from ventricular fibrillation/ventricular tachycardia arrest. Other inclusion criteria were age >18 and <76 and presumed cardiac etiology. Patients with other rhythms, known do not resuscitate/do not intubate, noncardiac etiology, significant bleeding, and terminal disease were excluded. The primary outcome was survival to hospital discharge with favorable neurological outcome. Patients (315 out of 331) who were resuscitated from VT/VF and transferred alive to the Emergency Department had complete medical records. Of those, 231 (73.3%) were taken to the CCL per the Minnesota Resuscitation Consortium protocol while 84 (26.6%) were not taken to the CCL (protocol deviations). Overall, 197 (63%) patients survived to hospital discharge with good neurological outcome (cerebral performance category of 1 or 2). Of the patients who followed the Minnesota Resuscitation Consortium protocol, 121 (52%) underwent percutaneous coronary intervention, and 15 (7%) underwent coronary artery bypass graft. In this group, 151 (65%) survived with good neurological outcome, whereas in the group that did not follow the Minnesota Resuscitation Consortium protocol, 46 (55%) survived with good neurological outcome (adjusted odds ratio: 1.99; [1.07–3.72], P=0.03). ConclusionsEarly access to the CCL after cardiac arrest due to a shockable rhythm in a selected group of patients is feasible in a large metropolitan area in the United States and is associated with a 65% survival rate to hospital discharge with a good neurological outcome.